Tax Planning Practices of Business Organizations on Baglung - Kandel, Ram Raja (Dhaulagiri Journal of Contemporary Issues, 2025)
This research explores the tax planning practices of business organizations on Baglung, Nepal, utilizing a causal-comparative research design. Employing a structured questionnaire with a Likert scale ranging from 1 (strongly disagree) to 5 (strongly agree), primary data was collected to investigates the impact of strategic tax planning, project tax planning, and action tax planning on overall tax planning. Additionally, the research explores the tax planning components and the overall tax planning effectiveness. It employed a primary data collection method through a well-structured questionnaire. A causal research design was adopted to examine the cause-and-effect relationship between independent variables (strategic tax planning, project tax planning, and action tax planning) and the dependent variable (tax planning). The results indicate a significant impact of strategic tax planning, project tax planning, and action tax planning on the overall tax planning effectiveness in business organization on Baglung. These findings contribute to the existing literature by providing insights into the specific tax planning practices that can enhance overall tax planning effectiveness in business organizations. The insights gained from this research contribute to the understanding of tax planning dynamics in the context of business organization on Baglung, Nepal. The implications of these findings can guide policymakers, tax professionals, and SMOs in enhancing their tax planning strategies, thereby fostering sustainable growth and compliance in the local business environment.